Eksplorasi Struktur Rajut dan Patchwork Crochet sebagai Praktik Kriya Tekstil Berkelanjutan pada Karya Busana Art Fashion Sustainability - Alyaa Aisyahra Bestari; Pipin Tresna P (Local History & Heritage, 2025)
This study investigates how knitted structures and patchwork crochet construction can be developed as a sustainable strategy for contemporary art fashion, addressing the growing demand for ethical and environmentally responsible design practices. The research problem centers on how traditional textile crafts may be transformed into innovative garment constructions that maintain aesthetic, functional, and ecological value. Using S. P. Gustami’s craft creation framework—exploration, design, realization, and evaluation—the study combines double crochet, bobble stitch, shell stitch, and loop stitch techniques into modular patchwork panels organized through color-blocking principles. The results show that this construction method produces garments that achieve structural coherence, visual expressiveness, and wearer comfort while reinforcing sustainability through handcrafted, low-waste production processes. Expert validation yielded an average score of 84.6 percent, classified as very good, indicating a high level of design quality and technical feasibility. The study concludes that patchwork crochet-based knitted structures provide a viable and conceptually rich approach for advancing sustainable art fashion by integrating cultural craft traditions with contemporary creative practices.